Inhibition of phosphodiesterase: A novel therapeutic target for the treatment of mild cognitive impairment and Alzheimer’s disease - Sheng, Jianwen; Zhang, Shanjin; Wu, Lule; Kumar, Gajendra; Liao, Yuanhang; GK, Pratap; Fan, Huizhen (Frontiers in Aging Neuroscience, 2022)
Alzheimer’s disease (AD) is the most common form of dementia and is ranked as the 6th leading cause of death in the US. The prevalence of AD and dementia is steadily increasing with an expected 14.8 million cases in the US by 2050. Neuroinflammation and a gradual neurodegenerative process develop in Alzheimer’s disease. However, no existing medications can stop, delay, or prevent disease progression. Phosphodiesterases (PDEs) are a wide family of enzymes that hydrolyze the 3′-phosphodiester links in cyclic adenosine monophosphate (cAMP) and cyclic guanosine monophosphate (cGMP) in signal-transduction pathways to produce 5′-cyclic nucleotides. They play crucial roles in many pharmacological activities, including proper cell functioning, by regulating the levels of cAMP and cGMP. Several evidence has suggested that abnormal cAMP signalling is linked to cognitive problems in neurodegenerative disorders like AD. Therefore, the PDE family has become a widely accepted and multipotential therapeutic target for neurodegenerative diseases. Notably, modulation of cAMP/cGMP by phytonutrients has a huge potential for the management of AD. Natural compounds have been known to inhibit phosphodiesterase by targeting key enzymes of cGMP synthesis pathway, however the mechanism of action and their therapeutic efficacy has not been explored extensively. Currently, few PDE inhibitors such as Vinpocetine and Nicergoline have been used for treatment of central nervous system disorders. Considering the role of flavonoids to inhibit PDE, we discussed the therapeutic potential of natural compounds with PDE inhibitory activity for the treatment of AD and related dementia.